Rotational Failure Mechanism for Face Stability of Circular Shield Tunnels in Frictional Soils - Yuan Zhou; Yuming Zhu; Shumao Wang; Hu Wang; Zhengxing Wang (Advances in Civil Engineering)
Face stability analyses of shield-driven tunnels are often carried out to determine the required support pressure on the tunnel face. Although various three-dimensional mechanisms have been proposed for circular faces of tunnels in frictional and/or cohesive soils to obtain the limit support pressure, the most critical one has not yet been found. Based on a rotational failure mechanism for the frictional soils, this paper modifies the circular cross section as an ellipse to make the generating collapse surface inscribe the entire circular tunnel face. Using the kinematical approach of limit analysis yields an upper bound to the limit support pressure. Through comparisons with the existing results in the literature, the improved mechanism can better estimate the upper bound and is very similar to the observed failures in the experimental tests. The influences of the pore water pressure are also included in the stability analysis of tunnel faces. Calculated upper-bound solutions are presented in a condensed form of charts for convenient use in practice.